The design of a scintillation system based on SiPMs integrated with gain correction functionality - Zhenhua Lin; Benoit Hautefeuille; Sung-Hee Jung; Jinho Moon; Jang-Guen Park (Nuclear Engineering and Technology, 2020)
Use of SiPM has been considered as an alternative to PMT, because of its compact size, low-operating voltage, non-sensitive to electromagnetic, low costs and so on. The main limitation for the use of SiPM is due to its small sensitive area compared to PMT that limits the light collection, and therefore the sensor energy resolution. In this article we studied the effect of increasing the number of SiPM by connecting them in parallel to increase the active detection area. This allowed us to compare the different energy resolution measurements. 137Cs has been selected as reference to study the energy resolution for 662 keV gamma-rays. Another investigation was to compare the minimum detectable gamma energy under various SiPM configurations. It has been found that the use of 4 SiPM arrays can greatly improve the energy resolution up to 4% than only one SiPM array, meanwhile use of more than 2 SiPM arrays does not increase the energy resolution significantly. Thus we can conclude that for a large area of cylindrical scintillator (3 × 3 inches), the use of SiPMs are limited to a certain number or certain active area depending on the commercial SiPMs, and its cost should be less than traditional PMT for the cost-effective and compact size considerations. It is well known that the gain of SiPM varies with temperature. In this article, we also calibrated gain to guarantee the same position of photoelectric peak in response of different temperatures. Keywords: SiPM configuration, Energy resolution, Minimum detectable gamma energy